2022
DOI: 10.1002/cam4.4582
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes in a cohort of oncologic patients with COVID‐19 during the first year of the pandemic in Mexico

Abstract: Background Literature on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in cancer patients is scarce in Latin America. This population seems to have a higher risk for adverse outcomes. This study aims to correlate clinical characteristics with outcomes in patients with cancer. Methods We included all patients with cancer and confirmed SARS‐CoV‐2 infection from April 19 to December 31, 2020, at the Instituto Nacional de Cancerologia, Mexico. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Another study conducted in the Mexican population, which included four hundred thirty-three patients with solid tumors (79%), hematological neoplasms (21%) and COVID19 from the National Cancer Institute of Mexico, reported one hundred thirty-five (31%), 131 (30%), and 93 (21%) patients had obesity, hypertension, and diabetes mellitus (DM), respectively and a mortality within 30 days after diagnosis of 18% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in the Mexican population, which included four hundred thirty-three patients with solid tumors (79%), hematological neoplasms (21%) and COVID19 from the National Cancer Institute of Mexico, reported one hundred thirty-five (31%), 131 (30%), and 93 (21%) patients had obesity, hypertension, and diabetes mellitus (DM), respectively and a mortality within 30 days after diagnosis of 18% [12].…”
Section: Discussionmentioning
confidence: 99%
“…An Israeli study reported a mortality rate of 20% in hematologic patients, before the Delta wave [ 25 ]. At INCan, we reported a cohort of non-vaccinated patients with Cancer and COVID-19, with a mortality rate of 18% [ 26 ]. Regarding Omicron, Taenaka et al reported an outbreak of 9 patients with HM in February 2022, with a mortality rate of 22% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al performed a multicenter retrospective chart review that included 233 COVID-19 patients with active cancer (Hem: n = 69, Tumor: n = 164). From a multivariable logistic regression adjusted for age, sex, race, obesity, D-dimer levels, and cancer treatment (no treatment vs. chemotherapy treatment in the past 3 months vs. other treatment), there was no statistically significant difference in odds of mortality between patients with hematological malignancies and solid tumors, although the directionality of the effect estimate favored patients with solid tumors (OR = 1.82 [95% CI: 0.88-3.77], p = 0.11) [29]. This study was deemed to be associated with a moderate risk of bias.…”
Section: Study-level All-cause Mortality Findingsmentioning
confidence: 92%
“…Twenty-one studies reported data on all-cause mortality [14,[24][25][26][27][28][29][30][31][32][33][34][35][36][39][40][41][42][43][44][45]. Of these, 4 studies were associated with a low risk of bias, 4 were associated with a moderate risk of bias, and 13 were associated with a high risk of bias.…”
Section: All-cause Mortalitymentioning
confidence: 99%